2008
DOI: 10.3155/1047-3289.58.4.543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Meteorological Parameters on Fine and Coarse Particulate Matter Mass Concentration in a Coal-Mining Area in Zonguldak, Turkey

Abstract: In this work, the effect of meteorological parameters and local topography on mass concentrations of fine (PM2.5) and coarse (PM2.5-10) particles and their seasonal behavior was investigated. A total of 236 pairs of samplers were collected using an Anderson Dichotomous sampler between December 2004 and October 2005. The average mass concentrations of PM2.5, PM2.5-10, and particulate matter less than 10 microm in aerodynamic diameter (PM10) were found to be 29.38, 23.85, and 53.23 microg/m3, respectively. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(42 citation statements)
references
References 27 publications
6
36
0
Order By: Relevance
“…Being the fraction of PM 10 , PM 2.5 is also high and showed higher correlation (Table 8). Similar correlations were found in the mining areas of Northern European countries (Tecer et al 2008). API was found to be highly correlated with PM 10 and PM 2.5 , which is indicative of the contribution of PM in API increment.…”
Section: Particulate Matter Concentrationssupporting
confidence: 76%
“…Being the fraction of PM 10 , PM 2.5 is also high and showed higher correlation (Table 8). Similar correlations were found in the mining areas of Northern European countries (Tecer et al 2008). API was found to be highly correlated with PM 10 and PM 2.5 , which is indicative of the contribution of PM in API increment.…”
Section: Particulate Matter Concentrationssupporting
confidence: 76%
“…Mbengue et al (2014) identified a bimodal distribution for an urbantraffic site, with peaks centered on 0.5 and 2.5 µm, whereas a trimodal distribution with a third maximum at 8 µm was only observed downwind of industrial emissions. Also Tecer et al (2008) attributed the most important anthropogenic PM 2.5-10 sources to the coal processing and mining industries located close and upwind to the sampling location.…”
Section: Ambient Pm Mass Concentration Size-distribution and Temporamentioning
confidence: 99%
“…For data treatment and analysis, results were differentiated into two main periods: the non-heating season (May 2015-October 15 th 2015) and the heating season (October 19 th 2015-March 2016), as is often performed in studies on atmospheric pollution (Tecer et al, 2008;Schwarz et al, 2012). For convenience, the separation between these periods was made in accordance with the switching on of the household heating systems during October 2015, as programmed by the Regional Directive of Lombardy.…”
Section: Statistical Analysis and Data Treatmentmentioning
confidence: 99%
“…Earlier studies (Aneja et al 2012;Hendryx 2009;Tecer et al 2008;Pless-Mulloli et al 2001) show that PM from different mining operations contributes to significant adverse effect on human health in the form of black lung, asthma, cardiovascular diseases and lung cancer. PM generated during mining operations at the workplace (called "bench") disperses in the mine by moving to several benches and contributes to the enhanced concentration at different parts of the mine .…”
Section: Introductionmentioning
confidence: 99%